Sudden cardiac death in athletes - Semsarian, C.; Sweeting, J.; Ackerman, M. J. (British Journal of Sports Medicine, 2015)
Sudden cardiac death is defined as an unexpected death, occurring usually within one hour from onset of symptoms in cases where the death is witnessed and in un witnessed cases within 24 hours of the individual last being seen alive and well. Sudden cardiac death in athletes is the leading cause of medical death in this subgroup, with an estimated incidence of 1 in 500 to 1 in 80 000 athletes per year, although a wide range has been reported, from 1 in 3000 in some subpopulations to 1 in 1 00 0000. Males, black or African Americans, and basketball players seem to be at a higher risk than other subgroups.